Increasing Import and Export Tonnage Through Sustainable Services and TMS Utilization - Basri Fahriza; Apsada Juhri; Yafi Raihan Fanshuria; Reyhan Rizqi Ressananta (Dinasti Review, 2025)
This study analyzes the effect of service continuity and the use of Transportation Management System (TMS) on increasing import and export tonnage at PT DHL Global Forwarding Indonesia. As part of DHL Global, the company focuses on providing consistent service and implementing TMS technology to improve operational efficiency. The results show that service continuity increases customer loyalty, while TMS contributes to operational optimization and cost savings, which together drive an increase in import and export tonnage. This study provides important insights to strengthen the company's operational performance and competitive position in the global market.